(NsINTAKSI^ESKIE OTNO[ENIQ W SLOVNOM PREDLOVENII (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NkUZNECOWA(B, (NrOZA dMITRIEWNAs ((NkALININ (B:s (NkALININSKOGO GOS(B. (NUN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE ST(B.s
(Nm(B-(NWO WYS[(B. (NI SRED(B. (NSPEC OBRAZOWANIQ rsfsr(B. (NkALININSKIJ GOS(B. (NUN(B-(NTs
Keywords: (NpREDLOVENIE W RUSSKOM QZYKEs; (NrUSSKIJ QZYK (B- (NsINTAKSISs